2018
DOI: 10.1016/j.compscitech.2018.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Smart cord-rubber composites with integrated sensing capabilities by localised carbon nanotubes using a simple swelling and infusion method

Abstract: Smart self-sensing composites with integrated damage detection capabilities are of particular interests in various applications ranging from aerospace and automotive structural components, to wearable electronics and healthcare devices. Here, we demonstrate a feasible strategy to introduce and localise conductive nanofillers into existing elastomeric coatings of reinforcing cords for interfacial damage detection in cord-rubber composites. A simple swelling and infusion method was developed to incorporate carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This is believed due to the tunnelling effect of electrons within the percolating network and the change in the distance between conductive fillers induced from external mechanical loading and deformation [41]. For what concerns the effect of strain amplitude on the self-sensing capability, the largest electrical resistance change was observed for the largest strain amplitudes, which is consistent with the mechanism of conductive network deformation based on percolated conductive networks [42].…”
Section: Self-sensing Capability Of Hdpe/gnp Nanocomposite Filmsupporting
confidence: 65%
“…This is believed due to the tunnelling effect of electrons within the percolating network and the change in the distance between conductive fillers induced from external mechanical loading and deformation [41]. For what concerns the effect of strain amplitude on the self-sensing capability, the largest electrical resistance change was observed for the largest strain amplitudes, which is consistent with the mechanism of conductive network deformation based on percolated conductive networks [42].…”
Section: Self-sensing Capability Of Hdpe/gnp Nanocomposite Filmsupporting
confidence: 65%
“…The electrical conductivity of the fabricated yarn could be further improved to 423.7 mS cm −1 by additionally depositing AgNPs. Using a modified dip coating process, Busfield and co‐workers proposed a straightforward method to fabricate conductive cords by incorporating CNTs into the elastomeric adhesive layer dip‐coated on the surface of glass fibers . Based on its electrical conductivity of 10 −2 S m −1 , the percolated CNTs network provided a self‐sensing ability for interfacial strain and damage in the cord‐rubber composites under the external stress.…”
Section: Fabrication Techniques For 1d Stretchable Electrodesmentioning
confidence: 99%
“…These aqueous dips involve latex offering necessary flexibility and reactivity to rubber and RF resin providing the desired heat and fatigue resistance by forming a three-dimensional network. [16][17][18][19] It has been also reported that the RFL treatment alone is not sufficient to modify the surface of high-performance organic fibers due to the lack of polar and hydrogen bonding groups in chemical structures. Hence, a dip-coating of functional adhesives prior to the treatment of RFL is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The cords are commonly treated with resorcinol‐formaldehyde‐latex (RFL) adhesives to improve the interfacial interaction with rubber. These aqueous dips involve latex offering necessary flexibility and reactivity to rubber and RF resin providing the desired heat and fatigue resistance by forming a three‐dimensional network 16–19 . It has been also reported that the RFL treatment alone is not sufficient to modify the surface of high‐performance organic fibers due to the lack of polar and hydrogen bonding groups in chemical structures.…”
Section: Introductionmentioning
confidence: 99%